Long-run Returns to Impact Investing in Emerging Market and Developing Economies - Cole, Shawn; Melecky, Martin; Molders, Florian; Reed, Tristan (World Bank, Washington, DC, 2020)
There is interest in impact investing, the idea of deploying capital to obtain both financial and social returns. But private financial returns are only possible if capital markets are not perfectly integrated, so profit opportunities still exist in certain markets. This proposition is put to the test by examining every equity investment made by one of the largest and longest-operating impact investors across 130 emerging market and developing economies. Since 1961 this portfolio has performed comparably to public and private equity in the United States, though it has under-performed since 2010. Investments in larger economies have higher returns, and returns decline as banking systems deepen and countries relax capital controls. These results are consistent with a core thesis of impact investing that some eligible markets do not receive sufficient investment capital.